2002
DOI: 10.1002/jnr.10257
|View full text |Cite
|
Sign up to set email alerts
|

Studies on neuronal death in the mouse model of Niemann‐Pick C disease

Abstract: A mouse model of Niemann-Pick disease type C (NPC) carries a genetic defect that causes biochemical changes in lipid levels and a progressive neuropathology that parallels the effects of NPC disease in humans. It is a moot point whether or not the loss of Purkinje and other neuronal cells proceeds by apoptotic death. Therefore, we have introduced into these mice a transgene expressing human Bcl-2 protein which has previously been demonstrated to prevent developmental neuronal death and death induced by a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…In keeping with these results, we observed cleaved caspase-3 and Fluoro-Jade C-positive Purkinje cells in the cerebellum but not in the hippocampus of Npc1 Ϫ/Ϫ mice. However, antiapoptotic strategies, such as overexpression of Bcl-2 or treatment with minocycline, that are known to prevent apoptosis in some models of neurodegenerative diseases failed to protect neurons in Npc1 Ϫ/Ϫ mice, 64 suggesting the possible existence of redundant apoptotic mechanisms in NPC pathology. Interestingly, our results revealed that the numbers of secondary lysosomes as well as of the autophagy markers LC3-II and beclin-1 are higher in both the cerebellum and hippocampus of Npc1 Ϫ/Ϫ mice compared with controls as reported in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with these results, we observed cleaved caspase-3 and Fluoro-Jade C-positive Purkinje cells in the cerebellum but not in the hippocampus of Npc1 Ϫ/Ϫ mice. However, antiapoptotic strategies, such as overexpression of Bcl-2 or treatment with minocycline, that are known to prevent apoptosis in some models of neurodegenerative diseases failed to protect neurons in Npc1 Ϫ/Ϫ mice, 64 suggesting the possible existence of redundant apoptotic mechanisms in NPC pathology. Interestingly, our results revealed that the numbers of secondary lysosomes as well as of the autophagy markers LC3-II and beclin-1 are higher in both the cerebellum and hippocampus of Npc1 Ϫ/Ϫ mice compared with controls as reported in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…In A-D, shown are the representative results, which were reproduced at least twice. Scale bars, 50 m. (Erickson and Bernard, 2002). A potential benefit of such a therapy against the human disease, however, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The comparisons made in the present study did not involve this region of brain. Other transgenic or knock-out mice in the C57BL/6 background have also been crossbred with the npc Ϫ/Ϫ BALB/c mice, without any noticeable effect on NPC pathology (Erickson and Bernard, 2002). All protocols and housing were approved by the Animal Care and Use Committee at the University of Washington.…”
Section: Methodsmentioning
confidence: 99%